PERENCANAAN PENAMBAHAN RELAY DIRECTIONAL EARTH FAULT (DEF) UNTUK GANGGUAN SATU FASA KE TANAH DI SALURAN 150 KV GARDU INDUK NUSA DUA – PESANGGARAN - G. A. P. Yuni Maheswari; I Gede Dyana Arjana; Cok Gede Indra Partha (Jurnal SPEKTRUM, 2021)
Disruption of short circuit flow of one ground phase that occurred on the transmissionline 150 kV Nusa Dua-Pesanggaran Substation, causing blackouts to occur in the Nusa DuaSubstation area extending to the surrounding area. The disruption that occurred failed to besecured because the GFR (Ground Fault Relay) relay could not detect the presence of a currentinterference so it failed to work. Assisted relays are needed to secure short circuit flowinterference one phase to help the GFR relay, where the selected relay is the DEF (DirectionalEarth Fault) relay. Installation of auxiliary relays requires planning and relay setting steps toobtain Iset, TMS and trip time. Calculations that have been done get the results of the GFR relayworking at a minimum interference of 1,200A while the DEF relay works at a minimuminterference of 0.521A. The one-phase disruption detected on the 150 kV channel based on thesimulation is below 300A. Def relay will work after the GFR relay does not manage to detectinterference of one phase of the land with a time span of 0 - 0.3 seconds.